PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL TERHADAP TRANSPARANSI LAPORAN KEUANGAN (Studi Kasus pada Dinas dan Badan Pemerintah Kota Lhokseumawe) - maryana (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2021)
This study aims to examine the Effect of Implementation of Accounting Standards Based on Accrual Government Transparency of Financial Statements (Case Study on Lhokseumawe City Government Agency). The data used in this research is primary data of 84 samples with purposive sampling technique. The method used to analyze between independent variable with dependent variable is simple linear regression method and classical assumption test. The result of the research is partial, the application of accrual accounting standard has a significant effect on the transparency of financial report on Lhokseumawe Government Agency.